2022
DOI: 10.3390/met12060982
|View full text |Cite
|
Sign up to set email alerts
|

Potentials for Describing Interatomic Interactions in γFe-Mn-C-N System

Abstract: Potentials for describing interatomic interactions in a γFe-Mn-C-N multicomponent system, modified Hadfield steel, where face-centered cubic (f.c.c.) iron is the main component, are proposed. To describe the Fe-Fe interactions in austenite, it is proposed to use Lau EAM potential. For all other interactions, Morse potentials are proposed, the parameters of which were found from various experimental characteristics: in particular, the energy of dissolution and migration of an impurity in an f.c.c. iron crystal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…From these derivations, it can be concluded that the correlation between bulk modulus and volumetric cohesive energy is applicable to any condensed matter on the condition that the potential energy landscape of chemical bonds can be approximated by the Morse potential. Fortunately, it has been demonstrated that the Morse potential can well describe the interatomic interaction for various condensed matter in both the equilibrium and dissociation states [28][29][30]. Therefore, a strong universality of the correlation between bulk modulus and volumetric cohesive energy can be expected.…”
Section: Resultsmentioning
confidence: 99%
“…From these derivations, it can be concluded that the correlation between bulk modulus and volumetric cohesive energy is applicable to any condensed matter on the condition that the potential energy landscape of chemical bonds can be approximated by the Morse potential. Fortunately, it has been demonstrated that the Morse potential can well describe the interatomic interaction for various condensed matter in both the equilibrium and dissociation states [28][29][30]. Therefore, a strong universality of the correlation between bulk modulus and volumetric cohesive energy can be expected.…”
Section: Resultsmentioning
confidence: 99%